Lexico-Semantic Features of Religious Terms - Feruza Khodjakulova Rustamovna (Genius Journals, 2022)
This paper examined the lexico-semantic features of language of religion and advertising. The study used relevant data from these two disciplines to show the lexical complexities and semantic inconsistencies or difficulties. Through this study, it has been discovered that both the language of religion and advertising have certain features in common such as being informative, eulogistic and persuasive, figurative, employing unusual collocation and deviant forms, employing emotive, adjectives and ungrammatical structures. The study also revealed that the language of religion and advertising differ from each other in that, religion still retains archaic forms while advertising employs simple words. Moreover, religion is wordy and dignified in nature while advertising is brief and casual. It is also observed that religion does not admit fragmentation and deviant spelling patterns but this is observed commonly in advertising. The study further shows that lexical and semantic features of language of religion and advertising distinguish them from everyday use of English language. Hence, features of language of religion and advertising are worth studying and are qualified for unique variety of the English language.
Keywords: Lexical; semantic features of language of religion; collocation